Analisis Kesalahan dalam Menyelesaikan Soal-Soal Matematika Ditinjau Dari Kemampuan Komunikasi Matematika Siswa SMP - Maya Nurlita; Asnila Asnila (Jurnal Akademik Pendidikan Matematika, 2022)
The formulation of the problem in this study was how the mistakes of VIII grade students of SMP Negeri 3 Buton Tengah in solving math problems in terms of mathematical communication skills on number pattern material. The purpose of this study was to find out how the mistakes of VIII grade students of SMP Negeri 3 Buton Tengah in solving math problems in terms of students' mathematical communication skills. This study was a qualitative research with a descriptive approach, where the number of research subjects were all students of class VIII A and class VIII B SMP Negeri 3 Buton Tengah. The instruments used in the form of tests, interviews, and documentation. Data analysis techniques used were data reduction, data presentation, data verification and examination of conclusions. Based on the results of this study using tests and interviews, it could be seen the types of errors made by students in the number pattern material based on their mathematical communication skills, namely: data errors, conceptual errors, operating errors, and errors not answering questions. The causes of student errors include: students were often wrong in entering data, students found it difficult to determine and used formulas, lack of accuracy in counting, and students were confused about what method to use to solve problems. Therefore, given alternative solutions after the first diagnostic test, after being given alternative solutions there was an increase in students' understanding and solving math problems on number pattern material based on their mathematical communication skills. So that, it could be concluded that there was a difference between test I and test II which had been given alternative solutions.